2019
DOI: 10.21037/qims.2019.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic nontuberculous mycobacterial granulomas in patients with cancer mimicking metastases: an analysis of three cases

Abstract: Hepatic granulomas caused by nontuberculous mycobacteria (NTM) are an uncommon, insidious, and indolent disease. Making an accurate diagnosis of a hepatic nontuberculous granuloma is challenging because of nonspecific clinical presentations and radiological appearances, especially in patients with a history of malignant tumors, as these lesions may mimic metastases and make a dilemma for decisionmaking in treatment. Herein, we report three cases of hepatic nontuberculous granulomas following operations for mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…NTM is the cause of numerous ailments, the most prevalent of which is lung infection. Additionally, NTM can induce cutaneous and soft tissue infection, musculoskeletal infection, lymphangitis, and disseminated infection 14,15,64 . In a retrospective study of patients with musculoskeletal infections caused by NTM, the most common microorganisms found to cause infections were MAC, M. fortuitum , and M. abscessus 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NTM is the cause of numerous ailments, the most prevalent of which is lung infection. Additionally, NTM can induce cutaneous and soft tissue infection, musculoskeletal infection, lymphangitis, and disseminated infection 14,15,64 . In a retrospective study of patients with musculoskeletal infections caused by NTM, the most common microorganisms found to cause infections were MAC, M. fortuitum , and M. abscessus 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NTM can induce cutaneous and soft tissue infection, musculoskeletal infection, lymphangitis, and disseminated infection. 14,15,64 In a retrospective study of patients with musculoskeletal infections caused by NTM, the most common microorganisms found to cause infections were MAC, M. fortuitum, and M. abscessus. 55 Our study found that various NTM species were also causative pathogens of PJI.…”
Section: Ntm and Common Related Diseasesmentioning
confidence: 99%
“…Nontuberculous Mycobacteria (NTM) are environmental organisms that are opportunistic in nature and under favorable conditions, cause a wide range of diseases ranging from pulmonary to disseminated infections, with the former being the most common [8]. Immune suppression is the typical predisposing factor and includes patients with HIV/AIDS, using immunosuppressive therapy and undergoing solid organ or haematologic transplant [9].…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, it mainly comprises macrophages, epithelioid cells and multinucleated giant cells, surrounded by a layer of T-lymphocytes [ 75 , 76 ]. Although NTM infections are more commonly associated with alveolar granulomas, disseminated NTM diseases sometimes result in granulomas in other parts of the body like the liver, especially in people with a history of tumors [ 77 ]. These structures present a major challenge to NTM drug therapy in two ways: they limit the penetration of the drugs into the bacteria inside the immune cells, and the anoxic conditions in the granuloma center promote physiological and morphological states that make them more tolerant [ 41 ].…”
Section: Mechanisms Of Drug Resistance In Nontuberculous Mycobactementioning
confidence: 99%